Efficacy of Topical Epinephrine in Tympanoplasty. (22nd June 2021) - List, Marna A.; Dirain, Carolyn O.; Haberman, Rex S.; Antonelli, Patrick J.
Abstract : Objectives/Hypothesis: To compare the hemostatic effects of commonly used concentrations of topical epinephrine in tympanoplasty. Study Design: Prospective, randomized, controlled clinical trial. Methods: Patients undergoing tympanoplasty were randomized to receive topical epinephrine at 1:1, 000 or 1:10, 000. With the investigators blinded, hemostasis was assessed with a modified Boezaart scale. Vasoconstriction was measured by laser Doppler. Blood pressure and pulse were tracked. Results: Thirty patients, 4 to 84 years old, were studied, with 15 patients per group. Boezaart scores dropped a mean of 67% and 62% with 1:1, 000 and 1:10, 000, respectively ( P  = .44). Capillary blood flow decreased a mean of 50.4% and 50.9% with 1:1, 000 and 1:10, 000, respectively ( P  = .95). The mean change in heart rate and mean arterial pressure after topical epinephrine exposure were −4.9 and −0.73 beats per minute ( P  = .15), and −0.60 and −0.73 mmHg ( P  = .96) for 1:1, 000 and 1:10, 000 respectively. No adverse events occurred in either group. Conclusions: Topical epinephrine at 1:10, 000 has hemostatic efficacy comparable to 1:1, 000 in tympanoplasty. Although both concentrations appear safe, use of topical epinephrine 1:10, 000 should be considered over 1:1, 000 to minimize the potential for adverse events. Level of Evidence: 2 Laryngoscope, 131:2319–2322, 2021